Effect of folic acid supplementation on homocysteine concentration and association with training in handball players - Molina-Lopez, J.; Molina, J. M.; Chirosa, L. J.; Florea, D. I.; Saez, L.; Planells, E . (Journal of the International Society of Sports Nutrition, 2013)
Strenuous physical activity can alter the status of folic acid, a vitamin directly associated with homocysteine (Hcy); alterations in this nutrient are a risk factor for cardiovascular disease. Handball players are a population at risk for nutrient deficiency because of poor dietary habits. Objective The aims of this study were to evaluate nutritional status for macronutrients and folic acid in members of a high-performance handball team, and determine the effect of a nutritional intervention with folic acid supplementation and education. Design A total of 14 high-performance handball players were monitored by recording training time, training intensity (according to three levels of residual heart rate (RHR): <60%, 60%--80% and >80%), and subjective perceived exertion (RPE) during a 4-month training period. Nutritional, laboratory and physical activity variables were recorded at baseline (Week 0), after 2 months of dietary supplementation with 200 mug folic acid (50% of the recommended daily allowance) (Week 8) and after 2 months without supplementation (Week 16). We compared training load and analyzed changes in plasma concentrations of Hcy before and after the intervention. Results Bivariate analysis showed a significant negative correlation (P < 0.01) between Hcy and folic acid concentrations (r = -0.84) at Week 8, reflecting a significant change in Hcy concentration (P < 0.05) as a result of hyperhomocysteinemia following the accumulation of high training loads. At Week 16 we observed a significant negative correlation (P < 0.01) between Hcy concentration and training time with an RHR <60%, indicating that aerobic exercise avoided abrupt changes in Hcy and may thus reduce the risk of cardiovascular accidents in high-performance athletes. Conclusion Integral monitoring and education are needed for practitioners of handball sports to record their folic acid status, a factor that directly affects Hcy metabolism. Folic acid supplementation may protect athletes against alterations that can lead to cardiovascular events related to exertion during competition.